Preparation method of solid electrolyte membrane structure

By mixing the solid electrolyte raw material with a binder and solvent and processing it with laser, the existing solid electrolyte membrane preparation method for solid state batteries is solved, and the simple, efficient and low-cost preparation of the solid electrolyte membrane is achieved.

CN119569440APending Publication Date: 2025-03-07MICROVAST INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411486578.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-08-30
Filing Date
2024-10-23
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing solid electrolyte membrane for solid state batteries is cumbersome and costly, and there is a lack of a simple, efficient and low-cost preparation method.

Method used

The solid electrolyte membrane structure is prepared by mixing the solid electrolyte raw material in proportion to form a mixture powder, and then mixing it with a binder and solvent to form a solid electrolyte precursor slurry, coated on the substrate and treated with laser.

Benefits of technology

This method simplifies the preparation process of solid electrolyte membrane, reduces costs, and improves production efficiency. The solid electrolyte membrane is closely bound to the matrix and has a flat structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569440A_ABST
    Figure CN119569440A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a solid electrolyte membrane structure body. The method comprises the following steps: S1, mixing solid electrolyte raw materials in proportion to obtain mixture powder; s2, mixing the mixture powder with a binder and a solvent to obtain solid electrolyte precursor slurry; s3, coating a base material with the solid electrolyte precursor slurry to obtain a solid electrolyte precursor coating; and S4, treating the solid electrolyte precursor coating by using laser to obtain the solid electrolyte membrane structure body.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related Applications

[0002] This application claims priority to U.S. patent application No. 18 / 822,018, filed on August 30, 2024, entitled “Method for Preparing Solid Electrolyte Membrane Structure,” which is hereby incorporated by reference in its entirety. Technical Field

[0003] The present application relates to the field of solid electrolyte technology, and in particular to a method for preparing a solid electrolyte membrane structure. Background Art

[0004] In the prior art, there are usually two methods for preparing solid electrolyte membranes for solid-state batteries: the first method is to prepare solid electrolyte membranes with raw materials on non-substrates such as non-current collectors or non-pole sheets, and then peel off the solid electrolyte membranes for assembling solid-state batteries. This method requires two or even more steps to apply solid electrolyte raw materials to batteries, and the operation steps are cumbersome; the other method is to directly coat the solid electrolyte finished product on the current collector (or pole sheet) and prepare the solid electrolyte membrane structure by laser melting. This method is costly. How to adopt a new method to make the preparation process of solid electrolyte membranes simple, efficient, and as low-cost as possible is a problem that technicians in this field should solve. Summary of the invention

[0005] According to various embodiments of the present application, a method for preparing a solid electrolyte membrane structure is provided.

[0006] A method for preparing a solid electrolyte membrane structure, comprising:

[0007] S1, mixing solid electrolyte raw materials according to proportion to obtain a mixture powder;

[0008] S2, mixing the mixture powder with a binder and a solvent to obtain a solid electrolyte precursor slurry;

[0009] S3, coating the solid electrolyte precursor slurry on a substrate to obtain a solid electrolyte precursor coating;

[0010] S4, treating the solid electrolyte precursor coating with a laser to obtain the solid electrolyte membrane structure.

[0011] In some embodiments, the solid electrolyte raw material includes a lithium source and a second metal source, wherein the second metal in the second metal source is selected from at least one of Al, Ti, Zr, La, Ta and Nb.

[0012] In some embodiments, the lithium source is selected from at least one of a lithium salt, lithium oxide, and lithium hydroxide; and the second metal source is selected from at least one of a second metal salt, a second metal oxide, and a second metal hydroxide.

[0013] In some embodiments, the lithium source is selected from at least one of lithium sulfate, lithium nitrate, lithium chloride, lithium oxide and lithium hydroxide; the second metal source is selected from Al 2 O 3 、TiO 2 、ZrO 2 ,La 2 O 3 、 2 O 5 , Nb 2 O 5 and La(NO 3 ) 3 At least one of .

[0014] In some embodiments, the solid electrolyte raw material further includes a phosphorus source, the phosphorus source is selected from phosphate, and the phosphate includes at least one of diammonium dihydrogen phosphate, ammonium phosphate, and diamine hydrogen phosphate.

[0015] In some embodiments, in step S1, mixing the solid electrolyte raw materials in proportion includes: grinding the solid electrolyte raw materials to obtain a mixture powder, wherein the average particle size of the mixture powder is less than or equal to 300 nm.

[0016] In some embodiments, in step S2, the mass ratio of the binder to the mixture powder is 1:100-5:95, and the binder is selected from at least one of polyvinylidene fluoride, epoxy resin, aramid and polytetrafluoroethylene.

[0017] In some embodiments, in step S2, the viscosity of the solid electrolyte precursor slurry is 2000 cPs-9000 cPs, and the solvent is selected from at least one of ethanol, acetone, nitrogen methyl pyrrolidone, isopropanol, ethyl acetate and dimethylacetamide.

[0018] In some embodiments, in step S3, the substrate includes a current collector or a pole piece.

[0019] In some embodiments, in step S4, before the solid electrolyte precursor coating is treated with a laser, a step of preheating the solid electrolyte precursor coating is also included, and the temperature of the preheating treatment is lower than the temperature at which the solid electrolyte precursor coating undergoes a chemical reaction and the temperature difference between the preheating treatment temperature and the temperature at which the solid electrolyte precursor coating undergoes a chemical reaction is less than or equal to 400°C.

[0020] In some embodiments, the preheat treatment is performed at a temperature of 400°C-800°C.

[0021] In some embodiments, the preheating treatment is a gradient preheating treatment.

[0022] In some embodiments, the gradient preheating treatment includes: first heating at a first heating rate of 1°C / min-20°C / min, and then heating to the preheating treatment temperature at a second heating rate of 20°C / min-50°C / min.

[0023] In some embodiments, in step S4, after reaching the preheating temperature, the temperature is maintained for 1 min-10 min, and then laser treatment is performed.

[0024] In some embodiments, in step S4, before the solid electrolyte precursor coating is treated with laser, the steps of drying and applying pressure to the coating are also included.

[0025] In some embodiments, in step S4, before the solid electrolyte precursor coating is treated with a laser, the porosity of the solid electrolyte precursor coating is 5%-40%.

[0026] In some embodiments, in step S4, before the solid electrolyte precursor coating is treated with a laser, the thickness of the solid electrolyte precursor coating is 5 μm-100 μm.

[0027] In some embodiments, in step S4, the wavelength of the laser is 900nm-1200nm, and the power is 20W-150W.

[0028] In some embodiments, in step S4, the solid electrolyte structure includes a substrate and a solid electrolyte membrane fixed on the substrate. After obtaining the solid electrolyte membrane structure, it also includes repeatedly coating the solid electrolyte precursor slurry on the solid electrolyte membrane to obtain a solid electrolyte precursor coating; and treating the solid electrolyte precursor coating with a laser to complete a chemical reaction step to increase the thickness of the solid electrolyte membrane.

[0029] The details of one or more embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to better describe and illustrate the embodiments and / or examples of those applications disclosed herein, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of any of the disclosed applications, the embodiments and / or examples currently described, and the best modes of these applications currently understood.

[0031] Figure 1 is a schematic diagram of a solid electrolyte membrane structure according to some embodiments of the present application;

[0032] Figure 2 This is the XRD diagram of the solid electrolyte membrane in Example 2 of the present application.

[0033] The symbols in the figure mean the following:

[0034] 10. solid electrolyte membrane structure; 100. solid electrolyte membrane; 200. substrate. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "or / and" used herein includes any and all combinations of one or more related listed items.

[0037] The present application provides a method for preparing a solid electrolyte membrane structure, comprising the following steps:

[0038] S1, mixing solid electrolyte raw materials according to proportion to obtain a mixture powder;

[0039] S2, mixing the mixed powder with a binder and a solvent to obtain a solid electrolyte precursor slurry;

[0040] S3, coating the solid electrolyte precursor slurry on the substrate to obtain a solid electrolyte precursor coating;

[0041] S4, treating the solid electrolyte precursor coating with a laser to obtain a solid electrolyte membrane structure.

[0042] The present application provides a method for preparing a solid electrolyte membrane structure. The solid electrolyte membrane structure of the present application comprises a substrate and a solid electrolyte membrane fixed on the substrate.

[0043] Compared with the prior art, the present application uses solid electrolyte raw materials to directly prepare a solid electrolyte membrane structure on a substrate, which saves raw material costs and simplifies the steps of preparing the solid electrolyte membrane structure; at the same time, in the solid electrolyte structure prepared in the present application, the solid electrolyte membrane is tightly combined with the substrate, and the solid electrolyte membrane structure is flat, which can be directly applied to subsequent production processes, helping to improve production efficiency.

[0044] In some embodiments, the solid electrolyte raw material includes a lithium source and a second metal source, wherein the second metal is selected from at least one of Al, Ti, Zr, La, Ta and Nb. The ratio of "mixing the raw materials in proportion" is determined according to the content of each element in the chemical formula of the solid electrolyte target component.

[0045] In some embodiments, the lithium source is selected from at least one of a lithium salt, lithium oxide, and lithium hydroxide; and the second metal source is selected from at least one of a second metal salt, a second metal oxide, and a second metal hydroxide.

[0046] In some embodiments, the lithium source is selected from at least one of lithium sulfate, lithium nitrate, lithium chloride, lithium oxide and lithium hydroxide; the second metal source is selected from Al 2 O 3 、TiO 2 、ZrO 2 ,La 2 O 3 、 2 O 5 , Nb 2 O 5 and La(NO 3 ) 3 At least one of .

[0047] In some embodiments, the solid electrolyte raw material further comprises a phosphorus source. In some embodiments, the phosphorus source includes but is not limited to phosphate. In some embodiments, the phosphate includes but is not limited to at least one of diammonium phosphate, ammonium phosphate, and diamine hydrogen phosphate.

[0048] In some embodiments, the ratio of the lithium source, the second metal source, and the phosphorus source is "mixed in proportion" and is determined according to the content of each element in the chemical formula of the target component of the solid electrolyte. 1.3 Al 0.3 Ti 1.7 P 3 O 12 For example, the lithium source can be Li 2 CO3 , the second metal source can be Al 2 O 3 、TiO 2 , the phosphorus source can be NH 4 H 2 PO 4 , according to the target component Li 1.3 Al 0.3 Ti 1.7 P 3 O 12 The number of elements in the chemical formula can be used to calculate the lithium source Li 2 CO 3 , the second metal source Al 2 O 3 、TiO 2 , phosphorus source NH 4 H 2 PO 4 The stoichiometric ratio of the components involved in the reaction can be flexibly adjusted to produce the desired target component.

[0049] In some embodiments, in step S1, mixing the solid electrolyte raw materials in proportion includes: grinding and mixing the solid electrolyte raw materials, adding a dispersion medium, and performing a grinding process to obtain a mixture powder, wherein the average particle size of the mixture powder (expressed by d50) is less than or equal to 300nm, or less than or equal to 200nm, or less than or equal to 100nm, or less than or equal to 50nm, or less than or equal to 20nm; the smaller the particle size, the more conducive to the reaction of the raw materials, making the reaction faster and more uniform.

[0050] In some embodiments, the grinding process includes but is not limited to ball milling and sand milling. In some embodiments, the dispersion medium includes at least one of ethanol and acetone. The time range of the grinding process is 5h-30h, or 8h-25h, or 12h-20h. After the grinding process is completed, the dispersion medium is removed to obtain a mixture powder.

[0051] In some embodiments, in step S2, the mass ratio of the binder to the mixture powder is 1:100-5:95, or 5:100, or 3:100. The binder is selected from at least one of polyvinylidene fluoride, epoxy resin, aramid and polytetrafluoroethylene. The addition of the binder can prevent the solid electrolyte precursor coating from cracking after the slurry solvent is dried in the later stage, and provide a precursor coating with a formed, tight and suitable porosity for laser operation. The amount of binder is related to the particle size of the mixture powder. The smaller the particle size, the larger the specific surface area, and the more binder is required; but the binder will decompose under the high temperature of the laser to form pores. If the mass ratio of the binder to the mixture powder is greater than 5:95, large pores are easily formed, which may cause scattering, and the accumulated heat may cause local overburning, which is not conducive to the formation of a uniform and dense solid electrolyte membrane.

[0052] In some embodiments, in step S2, the viscosity of the solid electrolyte precursor slurry is 2000cPs-9000cPs, or 2500cPs-8000cPs, or 3000cPs-7000cPs, or 3500cPs-6000cPs. In some embodiments, the mass percentage of the solvent to the mixture powder is 1:1-3:2, and the ratio range is the common solution preparation ratio range; the solvent is selected from at least one of ethanol, acetone, nitrogen methyl pyrrolidone, isopropanol, ethyl acetate and dimethylacetamide.

[0053] In the present application, the mixed powder is mixed with a binder and a solvent to obtain a solid electrolyte precursor slurry, which helps to make the solid electrolyte raw materials mix evenly; if the powder is not made into a slurry and laser sintering is directly used, powder scattering will occur.

[0054] In some embodiments, in step S3, the substrate includes a current collector or a pole piece.

[0055] In some embodiments, in step S3, the substrate comprises a negative electrode current collector or a negative electrode sheet comprising a negative electrode active material layer. In some embodiments, the negative electrode current collector is selected from at least one of copper, titanium-nickel alloy and nickel.

[0056] In some embodiments, in step S4, before the solid electrolyte precursor coating is treated with a laser, a step of preheating the solid electrolyte precursor coating is also included, and the temperature of the preheating treatment is lower than the temperature at which the solid electrolyte precursor coating undergoes a chemical reaction and the temperature difference between the preheating treatment temperature and the temperature at which the solid electrolyte precursor coating undergoes a chemical reaction is less than or equal to 400°C.

[0057] In the present application, a preheating step is used to reduce the temperature difference stress generated during the laser processing. Excessive temperature difference stress can cause the surface of the solid electrolyte membrane to bend, resulting in an uneven membrane surface, which affects the performance of the battery. When the temperature difference between the preheating temperature and the temperature required for the actual reaction of the raw materials to synthesize the product is greater than 400°C, it is not easy to reduce the temperature difference stress. In addition, by adopting a preheating step, substances that easily generate gas, such as adhesives, undried solvents, and easily decomposed raw materials, can be decomposed in advance to prevent bubbles from being generated during the laser scanning heating reaction to form a film. It should be noted that after the decomposition of the raw materials, elements that can participate in the subsequent chemical reaction of preparing the membrane will remain, which will not affect the formation of the final product.

[0058] In some embodiments, the temperature of the preheat treatment is 400°C-800°C, or 450°C-750°C, or 500°C-700°C, or 550°C-650°C, or 580°C, or 600°C.

[0059] In some embodiments, the preheating treatment is a gradient preheating treatment.

[0060] The gradient preheating treatment is as follows: firstly, the temperature is increased to the decomposition temperature of the binder and the raw material at a relatively low first heating rate (a heating rate that is too fast at the beginning will instantly trigger the decomposition process and cause large pores, so a slow heating method is adopted before the decomposition of the binder or the raw material), and then the temperature is kept at the decomposition temperature for a period of time. After the binder and the raw material are completely decomposed, the temperature is increased to the preheating treatment temperature at a slightly higher second heating rate to reduce the temperature difference stress generated by the laser.

[0061] It can be understood that the temperature rising process of the preheating treatment is related to the decomposition temperature of the binder used and the decomposable raw materials therein. In some embodiments, a relatively low first heating rate of 1°C / min-20°C / min, or 3°C / min-15°C / min, or 5°C / min-10°C / min can be used to heat the temperature to the decomposition temperature to prevent the decomposition speed from being too fast and generating large pores; after the binder and the raw materials are completely decomposed, the heating rate can be greater than 20°C / min, optionally, 20°C / min-50°C / min, or 25°C / min-50°C / min, 20°C / min-45°C / min, 20-40°C / min, 25°C / min-40°C / min, 30°C / min-35°C / min.

[0062] In some embodiments, in step S4, after reaching the preheating temperature, the temperature is kept for 1 min-10 min, or 3 min-7 min, or 5 min, and then laser treatment is performed.

[0063] In some embodiments, the preheating treatment includes preheating using an infrared furnace and preheating using a resistance furnace.

[0064] In some embodiments, the step of drying and applying pressure to the coating layer is further included before the solid electrolyte precursor coating layer is treated with a laser. By providing the steps of drying and applying pressure to the coating layer, the porosity and thickness of the solid electrolyte precursor coating layer can be controlled and adjusted.

[0065] It is understood that the drying method includes but is not limited to drying with a blower dryer and drying in an oven, as long as the solvent in the solid electrolyte precursor coating can be dried, no further restrictions are made here; the method of applying pressure to the coating in the present application includes but is not limited to roller pressing, as long as the porosity of the solid electrolyte precursor coating after applying pressure to the coating is 5%-40%, optionally 8%-35%, or 10%-30%, or 15%-25%, or 17%-20%. If the porosity of the solid electrolyte precursor coating is greater than 40%, the laser entering the interior of the coating is prone to scattering, heat accumulation, and local overheating; if the porosity is less than 5%, most of the laser will be reflected by the surface of the coating, and the heat is not easily absorbed by the interior of the coating, which may cause the interior of the coating to be difficult to fully complete the chemical reaction, and it is not easy to prepare a solid electrolyte membrane with high purity and a single structure.

[0066] In some embodiments, before the solid electrolyte precursor coating is treated with a laser, the thickness of the solid electrolyte precursor coating is 5μm-100μm, or 10μm-90μm, or 15μm-80μm, or 20μm-70μm, or 25μm-60μm, or 30μm-50μm. If the coating thickness is less than 5μm, the coating process difficulty of the aforementioned steps will increase. If the coating thickness is greater than 100μm, it will cause the bottom of the coating to be difficult to react completely. In the present application, the thickness of the solid electrolyte precursor coating is the thickness of the solid electrolyte precursor coating after pressure is applied to the coating.

[0067] In some embodiments, in step S4, the wavelength of the laser is 900nm-1200nm, or 950nm-1150nm, or 1000nm-1100nm, and the power of the laser scanning is 20W-150W, or 30W-130W, or 50W-100W, or 60W-90W.

[0068] According to the heat required for the reaction of different raw materials, the absorption coefficient of the bonding material and the wavelength characteristics of different instruments and equipment, the scanning speed can be further set to 2000mm / s-5000mm / s, or 2500mm / s-4500mm / s, or 3000mm / s-4000mm / s, the spot diameter is 0.1mm-0.15mm, the line spacing is 0-0.075mm, the defocus distance is 0-200mm, or 5mm-150mm, or 10mm-100mm, or 20mm-80mm, or 30mm-60mm, and the number of scans is 5 times to 50 times, or 10 times to 40 times, or 20 times to 35 times.

[0069] In some embodiments, in step S4, the wavelength of the laser is 1064nm, the power is 50W-150W, the scanning speed is 2000mm / s-5000mm / s, the spot diameter is 0.1mm-0.15mm, the line spacing is 0-0.075mm, the defocus distance is 0-200mm, and the number of scans is 5-50 times.

[0070] In the present application, through laser processing and utilizing the absorption characteristics of the material to the laser wavelength, the solid electrolyte precursor coating can be heated in a shorter time to undergo a chemical reaction to prepare a solid electrolyte membrane, thereby improving the reaction efficiency. The high temperature of the laser melts the surface of the metal substrate material, thereby ensuring a firm bond between the solid electrolyte membrane and the metal substrate.

[0071] In some embodiments, after obtaining the solid electrolyte membrane structure, it also includes repeatedly coating the solid electrolyte precursor slurry on the solid electrolyte membrane to obtain a solid electrolyte precursor coating; and treating the solid electrolyte precursor coating with a laser to complete a chemical reaction to form a new layer of solid electrolyte membrane, so as to increase the thickness of the solid electrolyte membrane.

[0072] like Figure 1 As shown, the present application also provides a solid electrolyte membrane structure 10. The solid electrolyte structure 10 includes a solid electrolyte membrane 100 and a substrate 200.

[0073] In some embodiments, the material of the solid electrolyte membrane 100 manufactured by the method of the present application is selected from Li 1.3 Al 0.3 Ti 1.7 P 3 O 12 (LATP), Li 7 La 3 Zr 2 O 12 (LLZO), Li 6.4 La 3 Zr1.4 Ta 0.6 O 12 (LLZTO), Li 6.5 La 3 Zr 1.5 Nb 0.5 O 12 (LLZNO), Li 6.8 La 3 Zr 1.6 Al 0.6 O 12 At least one of (LLZAO).

[0074] In some embodiments, the substrate 200 is selected from a current collector and a pole piece. In some embodiments, the substrate is selected from a negative electrode current collector or a negative electrode pole piece containing a negative electrode active material layer. In some embodiments, the material of the substrate 200 is selected from at least one of copper, titanium-nickel alloy, and nickel.

[0075] The present application also provides a method for preparing a solid electrolyte, comprising the following steps:

[0076] S1, mixing solid electrolyte raw materials according to proportion to obtain a mixture powder;

[0077] S2, mixing the mixed powder with a binder and a solvent to obtain a solid electrolyte precursor slurry;

[0078] S3, coating the solid electrolyte precursor slurry on the substrate to obtain a solid electrolyte precursor coating, drying, and peeling the solid electrolyte precursor coating from the substrate, rolling, and obtaining a solid electrolyte precursor film;

[0079] S4, treating the solid electrolyte precursor film with a laser to obtain a solid electrolyte sheet; and,

[0080] S5, grinding and crushing the solid electrolyte sheet to obtain a solid electrolyte.

[0081] In some embodiments, before the solid electrolyte precursor film is treated with laser in step S4, a step of preheating the solid electrolyte precursor film is also included.

[0082] The present application also provides a solid electrolyte prepared according to the above solid electrolyte preparation method, including but not limited to Li 1.3 Al 0.3 Ti 1.7 P 3 O 12 (LATP), Li 7 La 3 Zr 2 O 12 (LLZO), Li6.4 La 3 Zr 1.4 Ta 0.6 O 12 (LLZTO), Li 6.5 La 3 Zr 1.5 Nb 0.5 O 12 (LLZNO) and Li 6.8 La 3 Zr 1.6 Al 0.6 O 12 (LLZAO).

[0083] Example 1

[0084] Li and 2 CO 3 、Al 2 O 3 、TiO 2 and NH 4 H 2 PO 4 , add zirconium beads (the diameter of the zirconium beads is 0.2 mm) and dispersant ethanol, and sand grind for 5 hours. When the material particle size reaches d50 of 100 nm, separate the zirconium balls, dry the ethanol, and sieve to obtain a solid electrolyte precursor mixture powder.

[0085] Solid electrolyte precursor powder and PVDF were weighed at a mass ratio of 100:3, and NMP was added to obtain solid electrolyte precursor slurry. The solid electrolyte precursor slurry was coated on a metal copper foil, and the solid electrolyte precursor coating obtained after drying had a thickness of 70 μm, and then the coating layer was compacted, and the porosity of the solid electrolyte precursor coating was 20%; then laser scanning was performed, and the scanning laser conditions were: wavelength 1064 nm, power 70 W, scanning speed 4000 mm / s, spot diameter 0.15 mm, line spacing 0.075 mm, defocus distance 15 mm, scanning times 10 times, and a solid electrolyte membrane structure was obtained, and the membrane material of the solid electrolyte membrane structure was Li 1.3 Al 0.3 Ti 1.7 P 3 O 12 (LATP).

[0086] Example 2

[0087] Different from Example 1, before the laser scanning process, the copper foil coated with the solid electrolyte precursor coating was placed in an infrared furnace, heated to 400° C. at 10° C. / min, kept at 400° C. for 5 minutes, and then laser scanning was performed.

[0088] The solid electrolyte membrane of the solid electrolyte membrane structure is subjected to XRD test, see the attached Figure 2 It can be seen that this embodiment 2 can prepare Li with high purity and relatively complete structure. 1.3 Al 0.3 Ti 1.7 P 3 O 12 (LATP) solid electrolyte. The XRD test conditions are: scanning angle 10°-80°, scanning speed: 10° / min, step width: 0.02°.

[0089] Example 3

[0090] Different from Example 2, the power of the laser scanning is 10W.

[0091] Example 4

[0092] Li and 2 CO 3 ,La 2 O 3 、ZrO 2 The material was placed in a ball mill, zirconium beads and dispersant ethanol were added, and sand milling was performed for 5 hours. When the particle size of the material reached d50 of 300 nm, the zirconium beads were separated, and the ethanol was dried and sieved to obtain a solid electrolyte precursor mixture powder.

[0093] Solid electrolyte precursor powder and binder epoxy resin are weighed in a mass ratio of 95:5, and acetone is added to obtain solid electrolyte precursor slurry. The solid electrolyte precursor slurry is coated on a metal nickel sheet and dried. The thickness of the solid electrolyte precursor coating obtained after drying is 10μm, and then the coating layer is compacted. The porosity of the solid electrolyte precursor coating is 5%; the metal nickel sheet coated with the solid electrolyte precursor coating is placed in an infrared furnace, and the temperature is increased to 800℃ at 10℃ / min, and kept at 800℃ for 5min, and laser scanning is performed. The scanning laser conditions are: power 20W, scanning speed 4000mm / s, spot diameter 0.15mm, line spacing 0.075mm, defocus distance 10mm, scanning times 15 times, and a solid electrolyte membrane structure is obtained. The membrane material of the solid electrolyte membrane structure is Li 7 La 3 Zr 2 O 12 (LLZO).

[0094] Example 5

[0095] LiOH and La were weighed in a molar ratio of 6.4:1.5:1.4:0.3. 2 O3 、ZrO 2 and Ta 2 O 5 The material was placed in a ball mill, zirconium beads and dispersant ethanol were added, and sand milling was performed for 5 hours. When the particle size of the material reached d50 of 50 nm, the zirconium beads were separated, and the ethanol was dried and sieved to obtain a solid electrolyte precursor mixture powder.

[0096] Solid electrolyte precursor powder and epoxy resin are weighed in a mass ratio of 95:5, and acetone is added to obtain solid electrolyte precursor slurry. The solid electrolyte precursor slurry is coated on a metal nickel sheet and dried. The thickness of the solid electrolyte precursor coating obtained after drying is 100μm, and then the coating layer is compacted; the porosity of the solid electrolyte precursor coating is 30%; the nickel foil coated with the solid electrolyte precursor coating is placed in an infrared furnace, first heated to 400℃ at 10℃ / min, kept warm for 5min, then heated to 800℃ at 25℃ / min, kept warm at 800℃ for 5min, and laser scanning is performed. The scanning laser conditions are: power 150W, scanning speed 4000mm / s, spot diameter 0.15mm, line spacing 0.075mm, defocus distance 20mm, scanning times 15 times, and a solid electrolyte membrane structure is obtained. The membrane material of the solid electrolyte membrane structure is Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 (LLZTO).

[0097] According to Examples 1-3, it can be seen that the method of the present application can be used to prepare Li 1.3 Al 0.3 Ti 1.7 P 3 O 12 (LATP) solid electrolyte membrane. In some embodiments, since LATP cannot directly contact the lithium negative electrode, it is necessary to set another solid electrolyte membrane between the LATP solid electrolyte membrane and the nickel sheet, such as LLZO solid electrolyte membrane, that is, first prepare a layer of LLZO solid electrolyte membrane on the nickel sheet using the method of the present application, and then prepare the LATP solid electrolyte membrane on the LLZO solid electrolyte membrane using the method of the present application.

[0098] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0099] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.

Claims

1. A method for preparing a solid electrolyte membrane structure, characterized in that: include: S1, mixing solid electrolyte raw materials according to proportion to obtain a mixture powder; S2, mixing the mixture powder with a binder and a solvent to obtain a solid electrolyte precursor slurry; S3, coating the solid electrolyte precursor slurry on a substrate to obtain a solid electrolyte precursor coating; S4, treating the solid electrolyte precursor coating with a laser to obtain the solid electrolyte membrane structure.

2. The preparation method according to claim 1, characterized in that: The solid electrolyte raw material comprises a lithium source and a second metal source, wherein the second metal in the second metal source is selected from at least one of Al, Ti, Zr, La, Ta and Nb.

3. The preparation method according to claim 2, characterized in that: The lithium source is selected from at least one of a lithium salt, lithium oxide and lithium hydroxide; the second metal source is selected from at least one of a second metal salt, a second metal oxide and a second metal hydroxide.

4. The preparation method according to claim 3, characterized in that: The lithium source is selected from at least one of lithium sulfate, lithium nitrate, lithium chloride, lithium oxide and lithium hydroxide; the second metal source is selected from at least one of Al2O3, TiO2, ZrO2, La2O3, Ta2O5, Nb2O5 and La(NO3)3.

5. The preparation method according to claim 2, characterized in that: The solid electrolyte raw material further includes a phosphorus source, the phosphorus source includes a phosphate radical, and the phosphate radical is selected from at least one of diammonium dihydrogen phosphate, ammonium phosphate, and diammonium hydrogen phosphate.

6. The preparation method according to claim 1, characterized in that: In step S1, mixing the solid electrolyte raw materials in proportion includes: grinding the solid electrolyte raw materials to obtain a mixture powder, wherein the average particle size of the mixture powder is less than or equal to 300 nm.

7. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the binder to the mixture powder is 1:100-5:

95.

8. The preparation method according to claim 1, characterized in that: In step S2, the viscosity of the solid electrolyte precursor slurry is 2000 cPs-9000 cPs.

9. The preparation method according to claim 1, characterized in that: In step S3, the substrate includes a current collector or a pole piece.

10. The preparation method according to claim 1, characterized in that: In step S4, before the solid electrolyte precursor coating is treated with a laser, the step of preheating the solid electrolyte precursor coating is also included, and the temperature of the preheating treatment is lower than the temperature at which the solid electrolyte precursor coating undergoes a chemical reaction and the temperature difference between the temperature of the preheating treatment and the temperature at which the solid electrolyte precursor coating undergoes a chemical reaction is less than or equal to 400°C.

11. The preparation method according to claim 10, characterized in that: The temperature of the preheating treatment is 400°C-800°C.

12. The preparation method according to claim 10, characterized in that: The preheating treatment is a gradient preheating treatment.

13. The preparation method according to claim 12, characterized in that: The gradient preheating treatment includes: first heating at a first heating rate of 1°C / min-20°C / min, and then heating at a second heating rate of 20°C / min-50°C / min to the preheating treatment temperature.

14. The preparation method according to claim 10, characterized in that: In step S4, after reaching the preheating temperature, the temperature is kept for 1-10 minutes, and then laser treatment is performed.

15. The preparation method according to claim 1, characterized in that: In step S4, before the solid electrolyte precursor coating is treated with laser, the step of drying and applying pressure to the coating is also included.

16. The preparation method according to claim 1, characterized in that: In step S4, before the solid electrolyte precursor coating is treated with laser, the porosity of the solid electrolyte precursor coating is 5%-40%.

17. The preparation method according to claim 1, characterized in that: In step S4, before the solid electrolyte precursor coating is treated with laser, the thickness of the solid electrolyte precursor coating is 5 μm-100 μm.

18. The preparation method according to claim 1, characterized in that: In step S4, the wavelength of the laser is 900nm-1200nm, and the power is 20W-150W.

19. The preparation method according to claim 1, characterized in that: In step S4, the solid electrolyte structure includes a substrate and a solid electrolyte membrane fixed on the substrate. After obtaining the solid electrolyte membrane structure, it also includes repeatedly coating the solid electrolyte precursor slurry on the solid electrolyte membrane to obtain a solid electrolyte precursor coating; and treating the solid electrolyte precursor coating with a laser to complete a chemical reaction step to increase the thickness of the solid electrolyte membrane.